1993
DOI: 10.3109/15513819309048191
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pattern of Thy-1 Immunoreactivity in the Human Kidney and the Application to Pediatric Renal Neoplasms

Abstract: The localization of Thy-1, a surface membrane lipoglycoprotein, was investigated using a monoclonal antibody specific for human Thy-1 (HB-2S-1). The localization of Thy-1 during development was established in a series of five fetal, three childhood, and two adult normal kidneys. In this series, Thy-1 immunolocalization progressed from mesangial and endothelial cell staining in the 16- to 17-week fetuses to similar staining along with staining of the parietal epithelium of the capsule and proximal tubule staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These findings indicated that mesangial cells started to be formed from the S-shaped body in conjunction with Thy-1 expression; because podocyte folding and vascularization began to be seen in the S-shaped body stage, formation of mesangial cells may be related to podocytes and endothelial cells 23 . Here, we must take into consideration the difference in immunoreactivity of Thy-1 between rats and humans; human Thy-1 expression in mesangial cells is lost with renal development 24 . The expression patterns of mesangial cells for vimentin were similar to those for Thy-1 (Table 1), indicating the mesenchymal nature of the mesangial cells.…”
Section: Discussionmentioning
confidence: 98%
“…These findings indicated that mesangial cells started to be formed from the S-shaped body in conjunction with Thy-1 expression; because podocyte folding and vascularization began to be seen in the S-shaped body stage, formation of mesangial cells may be related to podocytes and endothelial cells 23 . Here, we must take into consideration the difference in immunoreactivity of Thy-1 between rats and humans; human Thy-1 expression in mesangial cells is lost with renal development 24 . The expression patterns of mesangial cells for vimentin were similar to those for Thy-1 (Table 1), indicating the mesenchymal nature of the mesangial cells.…”
Section: Discussionmentioning
confidence: 98%
“…PTHrP immunostaining was carried out using rabbit polyclonal C‐terminal PTHrP antiserum C6 (at 1:100 dilution; Izquierdo et al, 2006). To identify HMC, a rabbit polyclonal Thy‐1 antibody (Santa Cruz Biotechnology, Santa Cruz, CA), diluted 1:100, and a mouse α‐smooth muscle actin antibody (Sigma–Aldrich, St. Louis, MO), diluted 1:1,000, were used due to its relative specificity (Alpers et al, 1992; Bukovsky et al, 1992; Hazen‐Martin et al, 1993; Groma et al, 1997; Kuhara et al, 1997). Following incubation with the primary antibody, the sections were incubated with biotinylated anti‐rabbit IgG (Pierce, Rockford, IL), followed by incubation with the avidin‐biotin‐peroxidase complex (Dako, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…The glomeruli were cultured in D -Val-MEM supplemented with 20% fetal calf serum (Gibco Laboratories, Grand Island, N.Y., USA) and antibiotics (100 U/ml penicillin and 100 µg/ml streptomycin) at 37°C in a 5% CO 2 atmosphere to obtain mesangial cells for the experiments. The isolated rat mesangial cells used for the in vitro experiments were identified by their Thy-1 antigen expression [19], and mesangial cells from the seventh passage were used for our study.…”
Section: Methodsmentioning
confidence: 99%